THE EFFECTIVENESS OF IMPLEMENTATION OF SAK EMKM TO INCREASE ACCESS TO BANKING CAPITAL ON MSMES IN BOGOR REGENCY - Wahyuni, Iis; Sutomo, Hadi (Kesatuan Press, 2021)
ABSTRACT The purpose of this study is to measure the extent to which the implementation of SAK EMKM has been achieved by MSME entrepreneurs in Bogor Regency. to find out whether the preparation of financial reports in accordance with SAK EMKM can increase MSME banking access to capital, to find out what the obstacles and challenges faced by MSME entrepreneurs in implementing SAK EMKM at MSMEs in Bogor Regency. The results showed that the implementation of SAK EMKM that had been achieved in the Cibinong Raya area of ​​Bogor Regency was still low, namely 16.7%. Preparation of financial reports in accordance with SAK EMKM is very influential for MSME players in increasing access to MSME banking capital, it is proven that MSME actors who have prepared Financial Statements with SAK EMKM standards who apply for Bank loan access pass 100%, meanwhile, MSME players who had financial reports not yet standardized SAK EMKM who applied for access to loans from banks and other institutions passed only 23%. The obstacles and challenges faced by MSME entrepreneurs in implementing SAK EMKM are, many MSME players have received socialization about the preparation of SAK-EMKM-based financial reports, education level of MSME actors, the absence of on going training and mentoring in SAK-EMKM-based financial reporting training.